Knowledge and practice on pressure ulcer wound care among nurses working in the Philippines - Ramirez, Ma. Elena A.; Paredes, Chris N.; Reyes, Justine Ericca A.; Reyes, Leigh Nicole T.; Rivero, Christelle Danielle T.; Rocamora, Jessamyn E.; Simoy, Danessa C.
Background. For every 1,000,000 patients who developed pressure ulcer, 65,000 died from its complications (Agency for Healthcare Research Quality, 2008). Nurses play a key role in the management of pressure ulcer as they perform the assessment, cleaning, and dressing of wounds preventing such complications from occurring. The quality of wound care is highly dependent on the knowledge of nurses which is influenced by several factors. Their practice is also influenced by knowledge and other factors in their working environment. Thus, this study aims to determine the knowledge of nurses as well as its relationship with highest educational attainment, area of experience, years of experience, area of experience and formal trainings attended. Also, this study aims to describe the practice of nurses and determine its relationship with their working environment, namely staffing conditions, policies and guidelines and availability of supplies.